Pembentukan Sanggar Tani Muda Aksatani untuk Mendukung Regenerasi Petani Muda di Desa Sukowiryo, Kecamatan Jelbuk, Kabupaten Jember - Ayamilah, Yasaroti; Soetriono; Utami, Ratih Apri; Zahrosa, Dimas Bastara; Zaujiah, Rima; Prasetyo, Fahmi; Faradisi, Nurul Jinan; Adha, Iqlina Asmara; Resmi, Aji Dita; Hakim, Norma Kamilia; Halwiyah, Lailatul (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
Data from BPS (2023) shows that the number of farmers aged 19-39 years is 6,183,009 people or 21.39% of the total number of farmers in Indonesia. Sukowiryo Village is one of the villages that lacks farmer regeneration, which can threaten the sustainability of the agricultural sector. The PPK ORMAWA HIMASETA team held youth community service activities in Sukowiryo Village, Jelbuk District, Jember Regency, from March to August 2024. The community service activity aims to empower the interest and capacity of young farmers in Sukowiryo Village through the formation of a young farmer studio, 'AKSATANI'. The community service activity of the young farmer studio not only aims to be a forum for village youths to learn together but also plays a role in facilitating the development of more productive and sustainable agricultural businesses. The community service method used is the extension method. The AKSATANI program consists of a series of trainings, which include organisational management training, environmentally friendly cultivation, superior commodity processing, and digital marketing. Through the institution of the AKSATANI young farmer studio, the youth of Sukowiryo Village are given guidance in managing businesses, including the application of precision agriculture technology and smart farming. The results of the community service showed that the activities of the young farmer studio succeeded in increasing the knowledge and soft skills of young farmers in running farms.